Optimized Protocol for the Isolation of Spleen-Resident Murine Neutrophils - Coquery, Christine M. (2012)
Neutrophils are an important cellular component of the innate immune system that provides immediate protection to the host from infection. Neutrophil infiltration into inflamed peripheral tissues during infection is beneficial for immunity through phagocytosis of microbes, the release of antimicrobial factors, and secretion of proinflammatory cytokines. Recent reports further suggest that spleen-infiltrating neutrophils play a role in the adaptive immune response by providing survival signals to B cells. However, neutrophils may have detrimental effects on immunity in inflammatory diseases where their recruitment to lymphoid tissues and activation occur abnormally. To determine the contribution of neutrophils that reside in secondary lymphoid tissues to adaptive immunity, direct evaluation of the functional properties of tissue-resident neutrophils is required. We have developed a modified magnetic bead isolation approach for purifying neutrophils from inflamed spleens of autoimmune-prone mice by negative selection. Using this approach, we yielded neutrophils with greater than 90% purity without compromising cell viability. Equally important, the isolation procedure had little effect on the activation of neutrophils and did not impair phagocytic function. Thus, isolation of spleen-resident neutrophils by this optimized approach could be useful for interrogating the functional role of murine neutrophils in normal and abnormal immune responses.